Effect of Ethylene Oxide Sterilization on Humic Acid Modified Gelatin-Alginate Hydrogels - Velianyk, Vira; Strnadová, Katerina; Petrushenko, Sergey; Dukarov, Serhii; Sukhov, Volodymyr; Klochko, Natalja; Filenko, Olesya; Masikevych, Yurij; Repko, Kalif; Borovkov, Sergii; Lytvynenko, Oleksandr; Blyzniuk, Dmytro; et al. (Journal of Research Updates in Polymer Science, 2026)
The work is devoted to the clarification of the preservation of humic acid biomolecules encapsulated in biopolymer gelatin-alginate hydrogels during conventional sterilization with ethylene oxide (EO). According to SEM and EDS data, immediately after fabrication dried biopolymer hydrogels have smooth surface, layered structure and relatively uniform distribution of elements inherent in biopolymers C, O, N, and Na across all samples. According to the microbiological experiments, all of them contain a small number of fungi, but the contamination of Hana 2.5 and Hana 5 hydrogels with E. coli is high due to the encapsulated Hana biomolecules. The morphology of the biopolymer hydrogels was partially damaged but not completely destroyed after E. coli contamination and ethylene oxide sterilization according to SIST EN 550:2000. Moreover, microbiological tests for the detection of E. coli after ethylene oxide sterilization revealed the persistence of these bacteria due to the encapsulation with Gal, Nana 2.5 and Hana 5 hydrogels. Microbiological tests have shown sufficient resistance of the microbiota encapsulated inside gelatin-alginate biopolymer hydrogels to EO sterilization. In addition, it has been experimentally confirmed that the gelatin-alginate hydrogels modified with humic acids that we developed mainly retain their morphology and chemical composition during this sterilization.